Integral elements of a research protocol - Prashanthi Reddy; Upendra Singh Bhadauria (Wolters Kluwer Medknow Publications, 2019)
The research is conducted in accordance to a protocol that illustrates each essential part and the manner in which it is carried out. The research proposal outlines the key aim and provides numerous benefits to the researcher. There are numerous integral elements of a research protocol which ensure that the protocol is accurate, concise and provides adequate information about the study, ensures it is ethically sound, illustrates the need and the hypothesis of the study. The methodology explains the study design, procedures, and techniques used to achieve the proposed objectives. It defines the variables and demonstrates in detail how the variables will be measured, whereas the analysis plan and the statistical tests to determine the significance helps in rejecting or accepting the null hypothesis. Referencing is an extremely important aspect of the research protocol. A protocol with appropriate hypothesis, clear methodology, no typographical error, and easy readability is bound to create an impact on the existing and future literature.